Echium creticum (Boraginaceae), new adventive species in Argentina (Semiárida, 2020)
The presence of Echium creticum L. is recorded for first time in Argentina, in the south west of Buenos Aires province. This species is native from Creta island with 3 to 5 subspecies distributed along the Mediterranean Basin. This paper describes the species and inform about its presence in Sierra de la Ventana, Sierras de Cura Malal and surronding areas in Saavedra county.
Keywords: Echium; Buenos Aires; Argentina; adventitious flora;